2017
DOI: 10.1002/hep4.1020
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial composition can differentially regulate bile acid synthesis in humanized mice

Abstract: We previously reported that alcohol drinkers with and without cirrhosis showed a significant increase in fecal bile acid secretion compared to nondrinkers. We hypothesized this may be due to activation by alcohol of hepatic cyclic adenosine monophosphate responsive element‐binding protein 3‐like protein 3 (CREBH), which induces cholesterol 7α‐hydroxylase (Cyp7a1). Alternatively, the gut microbiota composition in the absence of alcohol might increase bile acid synthesis by up‐regulating Cyp7a1. To test this hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 25 publications
(47 reference statements)
3
29
0
Order By: Relevance
“…The initiating/central role of the intestinal microbiome in alcohol‐related disturbances of bile acid homeostasis has been demonstrated using humanized gnotobiotic mice . Germ‐free mice transplanted with stool from patients with cirrhosis with active alcoholism showed a higher ability to deconjugate and produce secondary bile acids in the stool with subsequent derangements of the bile acid homeostasis in several organs than germ‐free mice transplanted with stool from healthy subjects, similar to the human subjects themselves . This supports the importance of the deconjugating choloylglycine hydrolase family in the development of ALD.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The initiating/central role of the intestinal microbiome in alcohol‐related disturbances of bile acid homeostasis has been demonstrated using humanized gnotobiotic mice . Germ‐free mice transplanted with stool from patients with cirrhosis with active alcoholism showed a higher ability to deconjugate and produce secondary bile acids in the stool with subsequent derangements of the bile acid homeostasis in several organs than germ‐free mice transplanted with stool from healthy subjects, similar to the human subjects themselves . This supports the importance of the deconjugating choloylglycine hydrolase family in the development of ALD.…”
Section: Discussionmentioning
confidence: 58%
“…Alcoholics with cirrhosis have also been found to have higher fecal concentrations of hepatotoxic DCA and increased secondary to primary bile acid ratios in relation to healthy controls . The initiating/central role of the intestinal microbiome in alcohol‐related disturbances of bile acid homeostasis has been demonstrated using humanized gnotobiotic mice . Germ‐free mice transplanted with stool from patients with cirrhosis with active alcoholism showed a higher ability to deconjugate and produce secondary bile acids in the stool with subsequent derangements of the bile acid homeostasis in several organs than germ‐free mice transplanted with stool from healthy subjects, similar to the human subjects themselves .…”
Section: Discussionmentioning
confidence: 99%
“…This increase in secondary BAs is purported to be toxic to the intestinal barrier and could perpetuate alcoholic liver disease. Prior work has also shown that microbiota from an actively drinking human can replicate this BA profile after humanization of germ‐free mice who were not fed alcohol …”
mentioning
confidence: 97%
“…Before colonization, these were thawed, resuspended in 1.5 mL of sterile PBS per tube/pellet, and then gavaged 0.2 mL per mouse per day. In our prior studies, stool treated in this manner, once thawed and inoculated, could effectively colonize GF mice without complications and with good retention of bacterial profiles …”
Section: Methodsmentioning
confidence: 93%
“…Using established protocols that the NGRRC has developed and published, intact fecal material was transferred to 10‐15‐week‐old GF C57BL/6 mice (both male and female) by daily gavage for 3 days (6‐8 mice/group) . The mice were observed in sterile individually filtered cages for 15 days, after which they were harvested.…”
Section: Methodsmentioning
confidence: 99%